Recapitulation and Prospect of Research on Flow Field in Coal Mine Gob - Rui Zhang; Jianwei Cheng; Zui Wang; Zhenlu Shao (Shock and Vibration)
Coal mine gob, mined-out areas in underground coal mines, often accumulates explosive methane-air mixtures that pose a deadly hazard to miners. A good understanding of the flow field in a sealed coal mine area is crucial in preventing and minimizing accidents associated with mine combustible gases and also for planning and implementing a mine rescue strategy. In recent years, the research on the flow field in the gob has changed from qualitative research in the past to quantitative research. This paper synthesizes the research results of flow field in gob in recent 40 years, covering the permeability of quarried areas, the airflow simulation in quarried areas, and the influence of ventilation parameters and geohydrological conditions on the flow field. Firstly, the overburden failure mechanism and fracture development characteristics of the mine gob, the distribution of porosity and permeability in the gob, and the relationship between them are introduced. Secondly, the development of research methods and numerical models used to study the flow field in mine gob is discussed. The distribution of the flow field in the gob under different conditions is expounded. Thirdly, the research on the prevention and control of fire and explosion risks in the gob is discussed. Finally, the problems to be solved in such research direction are addressed and suggestions are put forward.